Pendampingan Pembuatan Detail Engineering Design Kantor Desa Sama Guna Kecamatan Tanjung Kabupaten Lombok Utara - Hafiz Hamdani; Muhammad Khalis Ilmi; Ari Ramadhan Hidayat; Agustini Ernawati; Titik Wahyuningsih; Anwar Efendy; Rajabi Mubarak; Rukayah Rukayah; Suwahip Suwahip; Aji Syailendra Ubaidillah; Intan Novianti; M. Sidik; Nura Safitri (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
Sama Guna Village is a division village located in Tanjung District, North Lombok Regency. By the formation of a new government institution, it is certainly not immediately supported by adequate facilities and infrastructure. One of them is the Village Office. In this case, Sama Guna Village wants to make a design related to the needs of the Village Office. However, this has become a quite tough activity for the Village based on: budget constraints, optimizing the utilization of Village funds and Village apparatus human resources. As a developer in the field of Civil Engineering and active in the field of development, as well as a form of scientific service to the community, assistance is needed to assisting activities for the engineered of the Village Office Detail Engineer Design (DED). Starting from activities: measurement; brainstorming with village and community officials; deliberations and assistance in the manufacture of DED, a design was found that is effective, strong and economical. The resulting building area is 313.96 m2.